Możliwości gromadzenia leśnych zasobów genowych w warunkach ex situ - Chmielarz, Paweł; Suszka, Jan; Bujarska-Borkowska, Barbara; Lewandowski, Andrzej; Wawrzyniak, Mikołaj; Kotlarski, Szymon; Hazubska-Przybył, Teresa; Litkowiec, Monika; Plitta-Michalak, Beata; Michalak, Marcin (Biuletyn Instytutu Hodowli i Aklimatyzacji Roślin, 2018)
-